2008
DOI: 10.1179/174328208x300732
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and morphological evidence on the status ofBryum mildeanumJur. and records revision in the Iberian Peninsula

Abstract: Bryum mildeanum, a rare species in the Iberian Peninsula, has frequently been confused with B. alpinum. In this study we provide new gametophytic and sporophytic (obtained by SEM) characters that can be used to separate the two and B. mildeanum is described and lectotypified. A molecular study based on two chloroplast DNA regions (trnL-F and trnG) was performed. The results suggest the evolutionary independence of B. mildeanum and B. alpinum, and the separation of both from B. gemmiparum, a species generally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Bryum mildeanum has been included in the genus Imbribryum based on molecular data published byGuerra et al (2008). Bryum torquescens and Bryum moravicum have not yet been sequenced, and although they are morphologically very close to Ptychostomum capillare, neither species has yet been transferred to this genus.Bryum moravicum Podp., V≥stn.…”
mentioning
confidence: 99%
“…Bryum mildeanum has been included in the genus Imbribryum based on molecular data published byGuerra et al (2008). Bryum torquescens and Bryum moravicum have not yet been sequenced, and although they are morphologically very close to Ptychostomum capillare, neither species has yet been transferred to this genus.Bryum moravicum Podp., V≥stn.…”
mentioning
confidence: 99%
“…Generic allocations based on morphology alone are therefore prone to error, some through convergent evolution of distant relatives, others by rapid change among close relatives. These findings have not been refuted by subsequent studies and parts of the sequence data used have been confirmed and supplemented by other workers (Guerra, Jiménez-Martínez, Cano, Brugués 2008; Guerra, Jiménez-Martínez, Cano, Jiménez-Fernández 2011; Wang and Zhao 2009; Bell, Long and Hollingsworth 2013). Thus the generic taxonomy adopted here is based mainly on molecular data.…”
Section: Author Citationsmentioning
confidence: 66%
“…At least seven locations (EOO= ca. 2950 km 2 ; AOO= 28 km 2 ) are known in Pyrenees and Montseny massif (Casas Sicart, 1960;Casanovas Poch, 1991;Guerra et al, 2008), where it occurs on wet soils and rocks, between 500 and 1950 m a.s.l. A report from Llorenç del Munt requires confirmation.…”
Section: Imbribryum Mildeanum (Jur) Jrspencementioning
confidence: 99%